Consequences of Heatwave on Density of Freshwater Turtle Populations in Water Plans of Northeastern Algeria - Frih, Abdelaziz; Ziane, Nadia; Hesni Benotmane, Kamelia; Hadiby, Rached (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
Aquatic turtles are ectotherm animals whose activities are conditioned by their environment. The objective of this study is to asses the heatwave effects on the abundance of aquatic turtles. The resulting study was conducted from spring to fall 2022, in a water plan next to Guerbes Sanhadja wetlands eco complex, known for the density of aquatic turtles it hosts. Temperature and rainfall data, as well as satellite images and field photography, were utilised to monitor the drying of the water plain. . Freshwater turtles were counted remotely every one hour from a specific location. The results obtained confirm the resumption of aquatic turtle activity, particularly marked in summer, but the persistence of heatwave, with abnormally high air temperatures and very low rainfall, caused the gradual drying up of the water plan and a sharp drop in turtle’s numbers.